2014
DOI: 10.14416/j.ijast.2014.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Diesel-waste Plastic Oil Blends on Engine Performance Characteristics

Abstract: The objective of this research is to present results of the performance (torque, power, thermal efficiency and specific fuel consumption) in a heavy-duty diesel engine when fueled with diesel-waste plastic pyrolysis oil (WPO) blends in full load condition. The tested engine is installed on an engine test bench and is attached with several sensors. The full factorial experimental design is performed to investigate both main and interaction effects. It is shown that fuel blends, engine speed and interaction of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…It was found that the mean absolute percentage errors were 1.95% and 5.38% for (2) and (3), respectively. An MAPE of lower than 10% confirmed that both quadratic models were very accurate (excellent prediction) [13][14][15].…”
Section: Accuracy Checkmentioning
confidence: 90%
See 1 more Smart Citation
“…It was found that the mean absolute percentage errors were 1.95% and 5.38% for (2) and (3), respectively. An MAPE of lower than 10% confirmed that both quadratic models were very accurate (excellent prediction) [13][14][15].…”
Section: Accuracy Checkmentioning
confidence: 90%
“…The differences between the measured and predicted values are the errors which can identify the accuracies of the generated quadratic models. Literature [12,13] suggests that mean absolute percentage error (MAPE) is generally used because it is a unit-free and is an easily understandable method. The MAPE is defined in (4).…”
Section: Accuracy Checkmentioning
confidence: 99%
“…Unburnt HC decreased with the increase of WPO blends . Above 75 volume percentage blends of WPO with diesel reduced the performance characteristics such as torque and power by 23.79% when specific fuel consumption was increased about 31.22% with reduced thermal efficiency up to 5.97% compared with diesel operations .…”
Section: Introductionmentioning
confidence: 93%
“…This can help mitigate some of the issues related to hazardous emissions caused by the disposal of discarded plastics. Many investigations are carrying by researchers on pyrolysis oil as an alternative to petroleum fuel [1]- [6]. The pyrolysis process is a waste plastic recycling process in which petroleum grade plastic oil is the critical byproduct.…”
Section: Introductionmentioning
confidence: 99%